Efficiency of Public Universities: The Role of Financial Autonomy in the Pandemic Situation - Yanuar Pribadi; Muhammad Heru Akhmadi; Irwanda Wisnu Wardhana (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2022)
This study measures the efficiency of public universities in the context of financial autonomy. The study explores 138 higher education in Indonesia with different levels of financial autonomy, including 12 fully autonomous, 52 semi-autonomous, and 74 non-autonomous universities. Using Data Envelopment Analysis and Analysis of Variance, the study revealed that more financial autonomy facilitates higher efficiency. In a similar vein, universities with higher efficiency scores are financially better than those with lower efficiency. We found that 3% of the universities are inefficient, due to the Covid-19 pandemic challenges. However, 23% of them experienced an increase in output while reducing their input. From this, we propose initiatives to develop financial autonomy for public universities.